AJPPS 2022
DOI: 10.25259/ajpps_5_2022
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between evidence-based practice and probiotic utilization among US adults: Results from a national survey

Abstract: Objectives: Recently published guidelines recommend probiotics for only a few indications. However, probiotics are widely utilized by consumers due to accessibility, perceived safety, and belief that they promote gut health. The objective of this survey study was to examine probiotic use, evaluate public knowledge regarding the risks and benefits of probiotics, and identify variables that predict the use of probiotics among US adults. Materials and Methods: The survey was conducted among a random sample of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…After conducting an extensive literature review, the survey was modelled and modified based on those used in previously published studies on the knowledge of probiotics [3][4][5][6][13][14][15]. This survey consisted of 18 questions, including multiple-choice, Likert scale, and response-free questions.…”
Section: Survey Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…After conducting an extensive literature review, the survey was modelled and modified based on those used in previously published studies on the knowledge of probiotics [3][4][5][6][13][14][15]. This survey consisted of 18 questions, including multiple-choice, Likert scale, and response-free questions.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…Probiotics are useful in the treatment of various gastrointestinal systemic diseases, effective in delaying the onset of allergic reactions in children, and useful in the treatment and prevention of vaginal and urinary tracts infections in women. Several studies have shown positive effects of probiotics on acute diarrhea, lactose intolerance, lowering serum cholesterol level, regulating immune system, and various diseases, including helicobacter pylori infection and cancer [4][5][6].…”
mentioning
confidence: 99%